Investigating the effectiveness of the architecture of the physical environment of Imam Reza Birjand Hospital on reducing patients\' pressure - Elahe Totabi; Reza Mirzaei; Mohsen Najmaddini (Tehran University of Medical Sciences, 2023)
Background and purpose: The physical environment of the hospital includes elements and components that improve the quality of the treatment environment and also reduce the stress of the patients. Therefore, this research aims to improve the environmental quality of treatment spaces with the approach of reducing patients' stress. Materials and methods: Based on the research approach, descriptive-analytical has been done. The selection of the research sample in the General Surgery Department (Imam Reza Birjand Hospital) is considered. To collect data, a questionnaire (patient, patient's companion, doctor and staff) was used to prioritize the variables. The validity of the questionnaire was checked by 3Smart PLS software, and the reliability was measured by Cronbach's alpha. Then the collected data was analyzed in SPSS 26 software. Results: The results of this study showed that the prioritization of different criteria from the physical factors of the indoor environment of therapeutic spaces including: convenience, flexibility, nature, light, color, fresh air, sound, texture, furniture arrangement, works of art, and scent are different. It is meaningful. Based on the Kruskal-Wallis test, the most significant difference in the patient's stress reduction priority is the criteria of color, material and texture, fresh air, scent. Based on the Yeoman-Whitney test, gender has a significant difference in the variables of scent, color and fresh air. Conclusion: The results of the research identified that flexibility, convenience, nature, according to the descriptive statistics, have the most influence in reducing the stress of the patients from the perspective of all the participant. Design solutions with the approach of reducing patient stress in medical centers are presented based on the significance of most variables.